Copper-Free Cleavage-Sonogashira Conjugation of Silylacetylene Immobilized Peptides - Strack, Martin; Metzler-Nolte, Nils; Albada, H. Bauke (Synthesis, 2014)
A one-pot copper-free fluoride-initiated method for the Sonogashira cross-coupling of SAM2-immobilized peptides is described.
Keywords: alkynes; peptides; solid-phase synthesis; Sonogashira; ylides